Pre-Fermentation of crushed Quebranta grape in the production of Pisco with separation of skins and seeds (LACCEI, 2024)
In the conventional process of elaboration of Pisco in Peru, the first operations of destemming and pressing, mainly the last one, are carried out avoiding the possibility of tearing the seeds and skins of the grape, which could denature the Pisco. In the destemming, the stalk is separated from the cluster, forming the crushed. This is pressed, obtaining must and a residue called pomace, which is very difficult to treat and separate for later use of its components. The pomace, together with other residues from the process, represent around 87% of the original grape. To achieve the effective separation of the pomace, without altering the brandy, a method and equipment for controlled pre-fermentation of the grape crushing are presented, eliminating the conventional pressing stage from the process. As a result of the proposed process, the effective separation of the seeds and shells is achieved, obtaining a greater amount of must, reducing the consumption of Quebranta grapes in the process from 6-8 kg of grapes/L of Pisco to 4 - 4.5 kg of grapes / L of Pisco. The physicochemical, organoleptic, and sensory characteristics of the Pisco obtained are within those required by the Denomination of Origin Regulation.